Perancangan Prototyping Sistem Informasi Penilaian Kinerja Dosen Perguruan Tinggi - Tanto Tanto; Fery Purnama; Ikbal Ramadhani (LPPM Politeknik Jambi, 2022)
Higher Education Governance is very important in achieving its Vision and Mission, one of which is in managing Human Resources (HR) in this case are Lecturers, Lecturers can carry out many tasks that are carried out both in the Tridarma of Higher Education and Structural, in this case many obstacles are faced faced in assessing lecturer performance, so far monitoring of work is still done manually still collecting hardcopy reports, and evaluating lecturer work takes a long time. In this research, a Prototyping Design of Higher Education Lecturer Performance Assessment Information System will be made that can be used to evaluate and evaluate the performance of Higher Education lecturers to support Accreditation where this system can be used as a reference in decision making. The next goal is to implement a lecturer performance appraisal system in tertiary institutions. Thus, higher education accreditation can be increased